Study of User Acceptance and Satisfaction of a Mandatory Government-Regulated Information System - Wibowo, Tony (CommIT (Communication and Information Technology) Journal, 2017)
This paper discusses the user acceptance of a mandatory government-regulated information system. The issue is investigated by using a modified UTAUTframework. From random sample data of 65 respondents, a regression model is established from which the conclusion is drawn. The study concludes that theaspects of performance expectancy, effort expectancy, social influence, and information system quality affect the user acceptance. The four aspects are equally important.